2000
DOI: 10.1037/0033-295x.107.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral responses to stress in females: Tend-and-befriend, not fight-or-flight.

Abstract: The human stress response has been characterized, both physiologically and behaviorally, as "fight-or-flight." Although fight-or-flight may characterize the primary physiological responses to stress for both males and females, we propose that, behaviorally, females' responses are more marked by a pattern of "tend-and-befriend." Tending involves nurturant activities designed to protect the self and offspring that promote safety and reduce distress; befriending is the creation and maintenance of social networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

158
2,035
22
49

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,794 publications
(2,264 citation statements)
references
References 212 publications
(264 reference statements)
158
2,035
22
49
Order By: Relevance
“…It has long been known that humans and other animals rely on social affiliation when under stress (Sapolsky et al 1997;Carter 1998;Panskepp 1998). The pituitary hormone oxytocin, which can be released by physical contact and affiliation, plays an important role in affiliationmediated stress reduction, and this effect is particularly pronounced in females (reviewed by Taylor et al 2000). In humans, women show a greater desire than men to seek social contact during times of stress, and they are also more likely to turn to smaller support groups (Taylor et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that humans and other animals rely on social affiliation when under stress (Sapolsky et al 1997;Carter 1998;Panskepp 1998). The pituitary hormone oxytocin, which can be released by physical contact and affiliation, plays an important role in affiliationmediated stress reduction, and this effect is particularly pronounced in females (reviewed by Taylor et al 2000). In humans, women show a greater desire than men to seek social contact during times of stress, and they are also more likely to turn to smaller support groups (Taylor et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary hormone oxytocin, which can be released by physical contact and affiliation, plays an important role in affiliationmediated stress reduction, and this effect is particularly pronounced in females (reviewed by Taylor et al 2000). In humans, women show a greater desire than men to seek social contact during times of stress, and they are also more likely to turn to smaller support groups (Taylor et al 2000). In both sexes, the number of 'core' individuals on whom people rely for support during times of crisis (3-5 individuals) tends to be significantly smaller than their circle of mutual friends (12-20) or regular acquaintances (30-50) (Dunbar & Spoor 1995;Hill & Dunbar 2003;Zhou et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Taylor and colleagues have suggested that the anxiolytic effect of OT upon the HPA axis constitutes an alternate pathway to 'fight or flight', which they have dubbed the "tend and befriend" response (Taylor et al, 2000;Taylor, 2006). This response promotes affiliative and social behaviour in response to stressful circumstances (Boutet et al, 2006;Engelmann et al, 2004;Lippert et al, 2003), maximising fitness through care (or 'tending') of offspring or others during periods of stress.…”
Section: Oxytocin and Stressmentioning
confidence: 99%
“…For example, some neuroendocrine products, such as the neuropeptide oxytocin (OT), may have positive effects on social behavior (e.g., Taylor et al, 2000;Zak et al, 2007). Further, there is evidence that experiencing positive emotions can improve a range of perceptual and performancebased behaviors (Fredrickson, 2001;Isen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…OT is a neurohypophyseal hormone that plays a role in social interactions and bonding (Taylor et al, 2000;Zak et al, 2007). Initial work on OT administration suggested that it may promote more positive social behavior, such as greater trust and generosity (Kosfeld et al, 2005;Zak et al, 2007), and more accurate social perception (Bartz et al, 2010a;Domes et al, 2007;Guastella et al, 2010).…”
Section: Introductionmentioning
confidence: 99%